Rheumatoid arthritis and Hailey-Hailey disease treated with methotrexate - Mestre, Beatriz (2022)
Publisher Copyright: © 2022 The Authors. International Journal of Rheumatic Diseases published by Asia Pacific League of Associations for Rheumatology and John Wiley & Sons Australia, Ltd.